Intervention Effects Work Motivation: The Effect Of Attitude And Work Environment On Service Quality - Rica, Julia Allen; Indramaharani, Yudhit; Irianto, Helena Parasiane; Kurniawigati, Indah; Hilmy, Reza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The problem that underlies this research is the infections that occur in inpatient installations for the period 2020 - 2021 which illustrates the problem of the quality of nurse services in inpatient installations. The purpose of this study was to prove the influence of attitudes and work environment on service quality with work motivation as an intervening variable. This type of research is included in quantitative research with a causality approach. The population is 148 nurses who work in inpatient installations, and the sample calculation uses the Slovin formula with an error rate of 5%, so that 110 samples are obtained as respondents using simple random sampling technique. The results of the analysis prove that attitudes and work environment partially and simultaneously have a positive and significant effect on service quality and work motivation, work motivation has a positive and significant effect on service quality and provides positive intervention on the relationship between attitude and work environment on service quality, so that with motivation work, attitude and work environment can improve service quality higher than without work motivation